New rock typing method for diagenetically modified carbonate reservoirs - E. Shvalyuk; A. Thistiakov; N. Bah; A. Mukhametdinova; A. Ryabukhin; M. Spasennykh (Georesursy)
The paper evaluates an efficiency of the existing rock typing methods for diagenetically modified carbonate reservoirs and proposes a new alternative rock typing index.Four existing rock typing techniques are applied to the target formation, subjected to considerable diagenetic alterations. Applied techniques do not provide sufficient results in terms of reliable correlation between porosity, permeability and irreducible water saturation, which is crucial for geological modelling. Therefore, a new rock typing index named KØS and calculated as a function of permeability (k), porosity (φ) and irreducible water saturation (Swir) is proposed for proper characterization of the carbonate formation. Contribution of depositional and diagenetic processes and associated microfeatures into parameters of the index is demonstrated by means of X-ray microCT and NMR experimental data.Comparative analysis of the proposed index with the existing ones shows that the KØS-derived rock types demonstrate the highest correlation coefficients between the key reservoir parameters. The defined rock types have distinguishable microstructures that confirm validity of the rock classification approach.All the entities of the KØS index are used for reserves calculations and commonly measured during routine core analysis: this enables its implementation at the most carbonate fields.